2021
DOI: 10.1002/ece3.7421
|View full text |Cite
|
Sign up to set email alerts
|

A community context for aggression? Multi‐species audience effects on territorial aggression in two species of Paridae

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 117 publications
(172 reference statements)
0
6
0
1
Order By: Relevance
“…However, animals' behaviours and interactions with each other and with other species in their broader community should perhaps be viewed as a web of interconnected influences and drivers that shape the social environment in which they live and behave [1,[30][31][32]. For example, territorial aggression in birds is strongly influenced by the number of heterospecific observers at contests [33]. To truly understand social influences, of which dominance is one, we need to consider not only the biotic and non-biotic environment (i.e.…”
Section: Mixed-species Groups Are Useful In Studying Dominance Becaus...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, animals' behaviours and interactions with each other and with other species in their broader community should perhaps be viewed as a web of interconnected influences and drivers that shape the social environment in which they live and behave [1,[30][31][32]. For example, territorial aggression in birds is strongly influenced by the number of heterospecific observers at contests [33]. To truly understand social influences, of which dominance is one, we need to consider not only the biotic and non-biotic environment (i.e.…”
Section: Mixed-species Groups Are Useful In Studying Dominance Becaus...mentioning
confidence: 99%
“…can influence MSGs from outside or within the group. For example, while predator–prey relationships are not included in any definition of MSGs, external threats from predators heavily influence MSG dynamics [33,54,55]. Many heterospecific associations may be driven in part by increased predation pressure [32,56,57], while some mixed-species behaviours are likely entirely a result of predator presence [58].…”
Section: Mixed-species Groups Are Useful In Studying Dominance Becaus...mentioning
confidence: 99%
See 1 more Smart Citation
“…En particular, en paseriformes se han descrito interacciones sociales agonísticas en torno a parches de recursos alimenticios y/o territorios establecidos (Sagario & Cueto 2014, Francis et al 2018, esto provoca la expresión comportamientos agresivos, incluyendo demostraciones de amenaza, dominancia, y ataques físicos directos (Francis et al 2018). No obstante, la expresión de conductas agonistas en aves suele variar entre especies de acuerdo a características morfológicas, genéticas, de historia de vida, y/o a características del ambiente, lo cual es materia de interés para la ecología del comportamiento (Maney & Godson 2011, Wojczulanis-Jakubas et al 2015, Davis & Sewall 2016, Hardman & Dalesman 2017, Bai et al 2021. En este contexto, el aporte experimental de alimento suplementario puede gatillar conductas agonísticas y de dominancia en diversas especies de aves (Foltz et al 2015, Wojczulanis-Jakubas et al 2015, Machovsky-Capuska et al 2016, Galbraith et al 2017.…”
Section: Short Communicationunclassified
“…Additionally, for successful chickadee flocks, the more diverse their MSG was, the quicker they were able to solve the task [29]. Subsequent experimental work has found that individual chickadee behaviour is influenced by the presence and number of titmice in their flocks [30] and that members of other species in these MSGs can influence aggressive behaviour of chickadees and titmice [31].…”
Section: Introductionmentioning
confidence: 99%